Perceptions of Threat to Religious Liberty. Issue 3 (15th July 2016) - Goidel, Kirby; Smentkowski, Brian; Freeman, Craig
ABSTRACT: Religious freedom in the United States is widely enjoyed and vigorously protected. Yet, a substantial percentage of Americans believe that their religious liberties are threatened. This article investigates the origins of these perceptions, focusing on the role of political orientations, religious identities and behaviors, social issues (i.e., gay marriage and abortion), and news attentiveness. We found that perceptions of threat are related to political orientations (i.e., partisan affiliation, ideology, and Tea Party identification) and issue positions (i.e., opposition to gay marriage). Consistent with theories of elite cue-taking, the effects of partisan affiliation are contingent on news attentiveness. Republicans who pay closer attention to the news are more likely to state that their religious liberties are threatened.